The Depression of Helen Knightly in The Almost Moon Alice Sebold's Novel - Anggarwani, Nidya; Kuncara, Singgih Daru; Rahayu, Famala Eka Sanhadi (Fakultas Ilmu Budaya Universitas Mulawarman, 2024)
This research focused on the depression experienced by Helen Knightly as the main character in Alice Sebold's The Almost Moon novel, which was published in 2007. Helen Knightly, the main character, is a nude model in an art department school who is familiar with mental health problems. The various incidents in her life made Helen traumatized and depressed, then she took unexpected actions. Therefore, this research aims to determine Helen's depression by using the depression theory of Aaron T. Beck to examine the kinds of depression in Helen. Furthermore, the researcher used a qualitative research method in this research. The data are generated from sentences, paragraphs, and dialogues that showed Helen's depression in the novel. Theoretically, there are seven in three mechanisms of the depression types, they are negative view about the world, negative view about the future, negative self-schemas, arbitrary inference, selective abstraction, personalization, and dichotomous thinking. The findings show that the depression was represented through characterization, namely: character as seen by another, speech, reactions, and thoughts. From the findings, it can be concluded that Helen's character is depressed, so she took unexpected actions such as killing her mother and dumping the body in a deep freeze, hiding, and having sex with her best friend's son, which then made Helen on the police wanted list. By looking at the case, the theory of depression is presented to understand the confusing behavior of the characters, as the term is an effort to raise the readers' awareness about depression.